2014
DOI: 10.1093/mp/ssu074
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of the Arabidopsis Response Regulator ARR18 with bZIP63 Mediates the Regulation of PROLINE DEHYDROGENASE Expression

Abstract: As the first and rate-limiting enzyme of proline degradation, PROLINE DEHYDROGENASE1 (PDH1) is tightly regulated during plant stress responses, including induction under hypoosmolarity and repression under water deficit. The plant receptor histidine kinases AHKs, elements of the two-component system (TCS) in Arabidopsis thaliana, are proposed to function in water stress responses by regulating different stress-responsive genes. However, little information is available concerning AHK phosphorelay-mediated downs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 92 publications
(127 reference statements)
4
43
0
Order By: Relevance
“…Pairwise protein sequence comparison revealed that PtRR19 and PtRR22 shared a good sequence identity with ARR12 (42.56%) and ARR10 (42.42%) respectively, linking up PtRR18 to ARR18 as plausible orthologs. In Arabidopsis, it has been reported an increase of ARR18 transcripts in leaves when the plants were submitted to an osmotic stress applied for six hours by a PEG 6000 treatment (Veerabagu et al, 2014). Based on these results, another attempt to isolate the RR18 in the Dorskamp genotype was conducted in experimental conditions which were reproduced according to this previous study.…”
Section: The Isolation Of Rr18 Was Achieved From Osmotic Stressed Popmentioning
confidence: 97%
See 4 more Smart Citations
“…Pairwise protein sequence comparison revealed that PtRR19 and PtRR22 shared a good sequence identity with ARR12 (42.56%) and ARR10 (42.42%) respectively, linking up PtRR18 to ARR18 as plausible orthologs. In Arabidopsis, it has been reported an increase of ARR18 transcripts in leaves when the plants were submitted to an osmotic stress applied for six hours by a PEG 6000 treatment (Veerabagu et al, 2014). Based on these results, another attempt to isolate the RR18 in the Dorskamp genotype was conducted in experimental conditions which were reproduced according to this previous study.…”
Section: The Isolation Of Rr18 Was Achieved From Osmotic Stressed Popmentioning
confidence: 97%
“…Similarly, here, the interactions of the newly isolated RR18 with the three HPts were validated, consistent with the ability of its homologous protein in Arabidopsis, ARR18, to establish intermolecular contacts notably with AHP1 , and protein sharing high sequence similarities with poplar HPt2, 7 and 9 (H ericourt et al, 2013). The conditions of its isolation, the interactions observed with downstream interacting HPt proteins of HK1 and the highlighted role of its homologous protein in Arabidopsis (Veerabagu et al, 2014) prompted us to study the regulation of RR18 expression in poplar cuttings submitted to osmotic stress during a six hours time-course. Although the levels of RR18 transcripts in different organs in control condition are relatively identical, they were increased in the leaves after 40 min of osmotic stress and so it went on until the end of the kinetic.…”
Section: Proteinmentioning
confidence: 99%
See 3 more Smart Citations